A focused information criterion for quantile regression: Evidence for the rebound effect - Peter Behl; Holger Dette; Manuel Frondel; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
In contrast to conventional model selection criteria, the Focused Information Criterion (FIC) allows for the purpose-specific choice of model specifications. This accommodates the idea that one kind of model might be highly appropriate for inferences on a particular focus parameter, but not for another. Using the FIC concept that is developed by BEHL, CLAESKENS, and DETTE (2014) for quantile regression analysis, and the estimation of the rebound effect in individual mobility behavior as an example, this paper provides for an empirical application of the FIC in the selection of quantile regression models. – – Im Gegensatz zu konventionellen Modellwahlkriterien erlaubt das Focused Information Criterion (FIC) die zweckgebundene Auswahl von Modellspezifikationen. Damit wird der Idee Rechnung getragen, dass ein Model höchst geeignet für die Schätzung eines bestimmten Fokusparameters sein kann, jedoch nicht für einen anderen Parameter. Dieser Artikel benutzt das FIC, das von Behl, Claeskens, und Dette (2014) für Quantilsregressionen entwickelt wurde und das Beispiel des Rebound-Effektes im Individualverkehr, um die Vorteilhaftigkeit des FIC bei der empirischen Modellwahl zu demonstrieren.
Keywords: C3; D2; 330; information criteria; fuel efficiency; price elasticities